Properly Identified Imaginary Needs, An Inaccurately Proposed Methodology: The Case of Rochester School of Accountancy's Positive Accounting Methodology - Khalid Al-Adeem (Journal of Accounting and Management Information Systems (JAMIS), 2021)
Research Question - Whether accounting research has been in a better status after the domination of Rochester School of Accountancy's Positive Accounting Methodology. Motivation - This study revisits the debate of the validity of Rochester school of accountancy's positive methodology. Rochester school of accountancy's positive accounting research has properly identified the assumed imaginary need of the US market. While positive accounting methodology may not be scientific under various accounts for science, it has contributed to accounting methodologically. Idea - Restricting financial accounting on issues related to decision-usefulness and perceiving corporate reporting as a product of accounting choices from an agency theory perspective constrains other dimensions of reality. Any restrictions to definitions of the role of accounting and its function (Glauter & Underdowen, 1974) blocks profoundly deep-rooted in contextual factors such as a country's social, political, and economic environment that all make up accounting which supposedly needs to be considered (Hellmann et al., 2010) in properly theorizing comprehensively practiced accounting. Data - Extensive writings have that documented internationally throughout time have been looked over. Tools - An analytical and critical examination has been conducted upon internationally accounting literature in a wide-ranging manner to provide an evaluation regarding Rochester school of accountancy's positive accounting research. Findings - The positive accounting methodology of the Rochester school of accountancy has been criticized by several accounting researchers for decades and even deem it disappointment and probably shame. Yet, Watts and Zimmerman declared themselves prime candidates. Its prevalence is the rhetoric of scientific inquiry. A measure of the failure of the so-called positive accounting methodology has achieved lays in its inability to become universal because differences in institutional environments persevere in the world. Contribution - Revisiting the debate of the validity of Rochester school of accountancy's positive methodology potentially contributes to our knowledge in assessing its legitimate prevalence in academic accounting research. New accounting researchers and scholars need to be aware of the predominant theoretical structure that governs the empirical financial paradigm and its limitation. This is especially significant to accounting researcher who has been intellectually trained under the positivistic tradition of economics.
Keywords: M14; M41; M42; M48; 650; Rochester School of Accountancy; Positive Accounting; Accounting Research; Research Methodology; Accounting Education; Rhetoric; Science; Theorizing; Theorization; Accounting Theory; Paradigm; Domination; Elitism; Role of Accounting